2016
DOI: 10.1155/2016/6850672
|View full text |Cite
|
Sign up to set email alerts
|

Relative Efficacy of Liquid Nitrogen Fertilizers in Dryland Spring Wheat

Abstract: The study was conducted in 2012 and 2013 at three locations in North Central and Western Montana (total of 6 site-years) to evaluate the relative efficacy of three liquid nitrogen (N) fertilizer sources, urea ammonium nitrate (UAN, 32-0-0), liquid urea (LU, 21-0-0), and High NRGN (HNRGN, 27-0-0-1S), in spring wheat (Triticum aestivumL.). In addition to at-seeding urea application at 90 kg N ha−1to all treatments (except for the unfertilized check plot), the liquid fertilizers were applied utilizing an all-terr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…However, damage of the flag leaf tips seems to be well tolerated by wheat, as confirmed by the appreciable yield and grain quality improvements reached by all foliar treatments, regardless of the fertilizer choice between UAN and urea. This is in agreement with the findings of several authors [11,24,26], while other studies [15,30] reported a higher threshold, i.e., 40 kg ha −1 as a single application between stages ZDS 39 (flag leaf visible) and ZDS 73 (early milk development), without compromising productivity.…”
Section: Discussionsupporting
confidence: 93%
“…However, damage of the flag leaf tips seems to be well tolerated by wheat, as confirmed by the appreciable yield and grain quality improvements reached by all foliar treatments, regardless of the fertilizer choice between UAN and urea. This is in agreement with the findings of several authors [11,24,26], while other studies [15,30] reported a higher threshold, i.e., 40 kg ha −1 as a single application between stages ZDS 39 (flag leaf visible) and ZDS 73 (early milk development), without compromising productivity.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, only in 3 of 8 site-years fertilization at N rate of 168 kg N ha −1 resulted in higher protein yield values, whereas grain yield did not respond to fertilization, whereas grain yield did not respond to fertilization above 56 kg N ha −1 at 4 of 8 site-years. Walsh and Christiaens (2016) reported the The Montana State University's recommendation (developed in the 1990s using the wheat N response trials carried out in the late 1970s-1980s) for dryland spring wheat is 1.5 kg N per 27 kg of wheat grain (Jacobsen, Jackson, & Jones, 2005). Considering these guidelines and the average grain yields of 4.8 Mg ha −1 , the optimum N rate for this study should have been 290 kg N ha −1 .…”
Section: Grain Yieldmentioning
confidence: 99%
“…In another N-response study in Montana, wheat yield was optimized with 120 kg N ha −1 ; in 4 of 8 site-years, yield did not respond to N rate above 56 kg N ha −1 (Walsh & Girma, 2016). A rate of 125 kg N ha −1 was adequate to optimize dryland spring wheat grain yield in Montana (Walsh and Christiaens (2016). The Montana State University N fertilizer recommendations are currently under review to address the changes in grower practices and higher NUE of recently released wheat varieties.…”
Section: Nitrogen Use Efficiencymentioning
confidence: 99%